Formulation, Characterization, and Herbal Drug Delivery Applications of Ethosome, Transfersome, and Transethosome - Luthfia Azzahra; Soraya Ratnawulan Mita; Sriwidodo Sriwidodo (Universitas Padjadjaran (Unpad), 2020)
Herbal compounds have different physicochemical properties. Its use on the oral route often has low biological availability. Therefore, alternative transdermal routes are used through the skin. The stratum corneum skin layer is the most difficult layer to penetrate. Therefore it is necessary to use a drug delivery system such as ethosome, transfersome or transethosome to increase transdermal drug delivery. This review article aims to look at the potential of ethosome, transfersome, and transethosome in increasing their ability to deliver herbal drugs in terms of their formulation and characterization. Literature searches were performed using online search engines namely NCBI and Google Scholar with the keywords ‘Transdermal Drug Delivery System’, 'Ethosome', 'Transfersome', and 'Transethosome'. The result showed compositions of ethosomes are phospholipids, water, and ethanol. The composition of transfersome is phospholipid, water, and edge activator. Transethosomes are a combination of phospholipids, water, ethanol, and edge activators. The role of ethanol and edge activator is thought to increase skin permeation. Transdermal drug delivery systems can be used on herbal drugs to increase transdermal drug delivery.Keywords: Transdermal, Ethosome, Transfersome, Transethosome, Herbal.